Roman Studies and Digital Resources. (23rd August 2018) - Bagnall, Roger S.; Heath, Sebastian
Abstract : There is hardly any aspect of scholarly work and teaching in Roman Studies today not marked by digital technology. We assume that readers regularly access digital images of Roman material culture, use digitised corpora of primary sources in the original language or translation or consult online books and articles. The availability of digital resources on the internet is also a welcome enabler of ongoing public interest and even participation in the field. This overall state of affairs is generally a positive development, but both general trends and specific digital resources deserve a critical appraisal.